La calidad de los servicios turísticos y la lealtad de los clientes en el Hotel Carrión de la ciudad de Loja - Pineda Escobar, Pablo Israel (2023)
As an accommodation company stands out from the competition and positions itself in the market, the quality of the services it provides is the main differentiator, and this is why it is crucial to conduct such studies that measure the loyalty it generates and the quality of its services. This research was developed with the purpose of measuring the quality of the services offered by the Hotel Carrión and the relationship that they have with the loyalty of its customers, specifically measuring the perception that customers have about the services provided by the hotel, the measurement of quality was done through the five dimensions, obtained through the SERVPERF model such as: Tangibility, Reliability, Responsiveness, Security and Empathy. Additionally, customer loyalty was measured through the four-dimensional model proposed by OLIVER, which are: Cognitive Loyalty, Affective Loyalty, Conative Loyalty or behavioral intentions and Action Loyalty, these two variables were analyzed to comply with the specific objectives proposed. Based on the methodology applied, methods and techniques, allowed to provide a basis for the proposed objectives. As a result of the correlational analysis of variables, it was possible to prove the alternative hypothesis, which is demonstrated through the results obtained, where it was determined that there is a high positive correlation between the quality of services and customer loyalty, concluding in this way that although there is a positive correlation in all dimensions, the different recommendations should be considered to improve them.